Media Digitalisasi Pembelajaran Jarak Jauh Menggunakan Model Blended Learning di Era Pandemi COVID 19 - Sri Rejeki; Dwi Budi Srisulistiowati (Jurnal Kajian Ilmiah, 2021)
Electronic learning (E-learning) is essentially an educational learning medium through the use of computer or internet technology, namely web-based learning technology (Web Based Instuc- tion). the implementation of e-learning is one part of alternative technology in helping to run the learning curriculum during the Covid 19 pandemic. aimed at knowing the process of implement- ing Blended Learning learning with google classroom XI-TKJ material class, to find out the per- ceptions of teachers and students towards the implementation of the COVID19 pandemic era google classroom learning. This research uses a qualitative method approach, the data sources in this study include primary and secondary data sources. Data collection techniques using the method of observation, interviews, and documentation. Checking the validity of the data using credibil - ity, transferbility, dependability, and confirmability.